Peran Sistem Pengendalian Manajemen dalam Meningkatkan Akuntabilitas Keuangan di Instansi Pemerintah - Rizal, Izzati (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
In the context of increasing demands for transparency and accountability in public sector financial management, understanding how management control systems influence financial accountability has become crucial particularly for State Universities with Legal Entity status (PTNBH), which operate under semi-autonomous governance with complex financial mechanisms. This study aims to examine the effect of management control systems on enhancing financial accountability in a government institution functioning as a PTNBH. A mixed methods approach was employed, involving 100 quantitative respondents through structured questionnaires and 10 qualitative informants via in-depth interviews. The quantitative analysis reveals a positive and significant effect of management control systems on financial accountability, with a regression coefficient of 0.63 (p < 0.001). The qualitative findings support the quantitative results, highlighting the essential roles of leadership commitment, human resource competence, and effective use of information technology in improving control system effectiveness. The novelty of this study lies in its focus on the PTNBH governance model, which introduces unique accountability challenges. The research suggests that strengthening human resource capacity and developing information technology infrastructure are strategic measures to enhance financial accountability. Future studies are recommended to investigate the role of organizational culture and to develop digital-based control system models tailored to higher education institutions.